An improved simple rat model for global cerebral ischaemia by induced cardiac arrest. (2nd April 2016) - Frick, Tamara; Springe, Dirk; Grandgirard, Denis; Leib, Stephen L.; Haenggi, Matthias
Abstract : Objectives: Cerebral hypoxic-ischaemic injury following cardiac arrest is a devastating disease affecting thousands of patients each year. There is a complex interaction between post-resuscitation injury after whole-body ischaemia-reperfusion and cerebral damage which cannot be explored in in vitro systems only; there is a need for animal models. In this study, we describe and evaluate the feasibility and efficiency of our simple rodent cardiac arrest model. >Methods: Ten wistar rats were subjected to 9 and 10 minutes of cardiac arrest. Cardiac arrest was introduced with a mixture of the short-acting beta-blocking drug esmolol and potassium chloride. Results: All animals could be resuscitated within 1 minute, and survived until day 5. General health score and neurobehavioural testing indicated substantial impairment after cardiac arrest, without differences between groups. Histological examination of the hippocampus CA1 segment, the most vulnerable segment of the cerebrum, demonstrated extensive damage in the cresyl violet staining, as well as in the Fluoro-Jade B staining and in the Iba-1 staining, indicating recruitment of microglia after the hypoxic-ischaemic event. Again, there were no differences between the 9- and 10-minute cardiac arrest groups. Discussion: We were able to establish a simple and reproducible 9- and 10-minute rodent cardiac arrest model with a well-defined no-flow-time. Extensive damage can be found in the hippocampus CA1 segment. The lack of difference between 9- and 10-minute cardiac arrest time in the neuropsychological, the open field test and the histological evaluations is mainly due to the small sample size.